Plenty of penguins - Black, Sonia; MacCombie, Turi (New York : Scholastic, 1999)
Illustrations and brief text describe different kinds of penguins.
1.0
K-3
Keywords: Penguins -- Juvenile literature; Penguins; Penguins; Penguins